Difficulties in localization and treatment of insulinomas in type 1 multiple endocrine adenomatosis (MEA). Issue 797 (March 1992) - Winocour, P. H.; Moriarty, K. J.; Hales, C. N.; Adams, J.; Reeve, R.; Wynick, D.; Allison, D.; Bloom, S. R.; Anderson, D. C.
Abstract : A 15 year old girl with a family history of type 1 multiple endocrine adenomatosis presented with reversible neurological disturbances, hypoglycaemia and hyperinsulinaemia. Initial radiology was normal, but portal venous sampling suggested an insulinoma in the tail of the pancreas which was removed with conservation of the spleen. Hypoglycaemia persisted despite high doses of diazoxide and intravenous dextrose. A second laparotomy revealed a pancreatic endocrine tumour and sub-total pancreatectomy was performed. Histology revealed islet cell microadenomatosis. Hypoglycaemia persisted despite treatment with somatostatin analogues and 40% intravenous dextrose was required to maintain normoglycaemia. A possible lesion near the splenic hilum on computed tomographic scan was reported as a splenunculus although further peripheral, hepatic and portal venous sampling suggested hepatic or systemic lesions. A positron emission scan and selective visceral angiography suggested a lesion in the left upper quadrant. Acute lactic acidosis, rhabdomyolysis and renal failure supervened. Post mortem revealed the putative 'splenunculus' to be a residual insulinoma, whilst the splenic vein was thrombosed, accounting in part for discrepant venous sampling data. Hyperinsulinaemia in type 1 multiple endocrine adenomatosis may require more aggressive surgical and hormonal intervention than when dealing with solitary insulinomas. Insulinomas may mimic developmental abnormalities on computed tomographic scanning.